Experimental evaluation and computational simulation of the dissolution of sodium chloride particles in a brine fluid flow - Scheid, Cláudia Miriam; Patrão, Wanderson; Silva, Renata; Martinsen, Kristoffer Harr; Magalhães, Sérgio da Cruz; Calçada, Luis Américo (Acta Scientiarum. Technology, 2014)
A mathematical model to predict the dissolution of salt particles suspended in a brine flow is provided. The model consists of a system of three partial differential equations (PDE) based on mass conservation of salt dissolved in the fluid phase, on mass conservation of salt particles in the solid phase and on the overall conservation of energy. A fluid flow experimental unit was built to determine the kinetics of the dissolution of salt particles in a brine flow. Fluid samples free from particled solid material retrieved through the flow line at several predefined points were collected to determine salt dissolution profile. The global convective mass transfer coefficient was evaluated based on the experimental data. Simulations validated the mathematical model and relative deviations between experimental data and simulations were less than 10%. Â 